Understanding a digital movement of opinion: the case of #RefugeesWelcome. Issue 8 (3rd July 2019) - Barisione, Mauro; Michailidou, Asimina; Airoldi, Massimo
ABSTRACT: Recent work on digital political engagement has extensively shown that social media platforms enhance political participation and collective action. However, the idea that citizen voice through social media can give rise, under given conditions, to a specific digital force combining properties of social movements and public opinion has received less attention. We fill this gap by analysing the digital discussion around the Twitter hashtag #RefugeesWelcome as a case of 'digital movement of opinion' (DMO). When the refugee crisis erupted in 2015, an extraordinary wave of empathy characterized the publics' reactions in key European hosting countries, especially as a result of viral images portraying refugee children as the main victims. Using a triangulation of network, content and metadata analysis, we find that this DMO was driven primarily by social media elites whose tweets were then echoed by masses of isolated users. We then test the post-DMO status of the hashtag-sphere after a potentially antithetical shock such as the November 2015 Paris terrorist attacks, which polarized the network public. Overall, we argue that the concept of DMO provides a heuristically useful tool for future research on new forms of digital citizen participation.